Open Thoracic Anterolateral Cordotomy – Is There Still Room? - Lyra, Carlos Alberto Miranda; Araujo, Ângelo Marcel Santana Duarte; Júnior, Dimas Fernandes Vasconcelos; Sá, Danilo Medeiros Menezes; Oliveira, Arthur Maynart Pereira; Morais, Rilton Marcus; Hamani, Clement; Iglesio, Ricardo Ferrareto; de Andrade, Daniel Ciampi; da Cunha, Pedro Henrique Martins; Lapa, Jorge Dornellys da Silva (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Cancer pain encompasses multiple mechanisms, thus falling under the classification of mixed pain. Cordotomy for oncologic pain has been performed since a long time ago, as an open surgical technique or a percutaneous approach.We describe here the successful application of an open thoracic cordotomy to treat a young patient with advanced cervical cancer. Additionally, a scoping review was conducted, focusing on the efficacy of open cordotomy for the treatment of cancer pain.Following PRISMA guidelines, Medline and Embase were searched for articles reporting open cordotomy to treat mainly oncologic pain. Event rates related to pain and adverse events were recorded and amalgamated between studies. Studies written in English, Portuguese, or Spanish, and published between 1960 and 2023 were included.Of 495 abstracts retrieved, 22 articles were selected for full-text review, of which 10 manuscripts ultimately met inclusion criteria and were pooled for review. A total of 305 patients treated with an open cordotomy were reported in 10 articles, a complete or partial relief of the pain was present in 90% of the patients and only 10% showed a bad pain response after the procedure. Urinary incontinence, motor weakness, and death have been reported in 13%, 7,5%, and 3% of the studies, respectively.Pain improvement was observed in patients who underwent open cordotomy with an acceptable risk of complications. However, prospective studies in the area are needed to confirm efficacy. Furthermore, new technologies should be explored for tailoring open cordotomy.
Keywords: chronic pain; spinal cord; cordotomy; cancer pain